Perancangan Sistem Administrasi bagi Sekretaris Kamar dalam Mewujudkan Profesionalisme Organisasi di Pondok Pesantren Naungan Yayasan Islam Al-Ghozali Krempyang Tanjunganom Nganjuk - Ahmad Saifudin; M. Yusuf (LP3M STAI Darussalam Krempyang Nganjuk, 2020)
Assistance in the design of administrative systems for room secretaries after extracting data about secretarial matters. In the social analysis it was found that in the management of the room there had never been guidance for the room secretary in a standard way, the coaching was limited to daily operations. If the administration in the room is not managed properly, then the management will not run optimally. This activity will solve problems regarding administration with the aim of providing direction, coaching and assistance to room secretaries of the Miftahul Mubtadiin ar Ridlo, al Hamami and an Nur Islamic Boarding School. Pesantren is a place of learning, including administrative activities. The santri room is also a community where management and professional organizational principles need to be applied. However, all training, socialization and administrative guidance from the lodge are only in the form of daily operations, not yet at the evaluation stage of how these activities are carried out properly so that the room secretary can work professionally with the principles of organizational administration, training is necessary so that they can carry out their duties effectively and efficiently.